A New High-Quality Draft Genome Assembly of the Chinese Cordyceps Ophiocordyceps sinensis. (24th June 2020) - Shu, Ruihao; Zhang, Jihong; Meng, Qian; Zhang, Huan; Zhou, Guiling; Li, Miaomiao; Wu, Peipei; Zhao, Yanni; Chen, Chao; Qin, Qilian
Abstract: Ophiocordyceps sinensis (Berk.) is an entomopathogenic fungus endemic to the Qinghai-Tibet Plateau. It parasitizes and mummifies the underground ghost moth larvae, then produces a fruiting body. The fungus-insect complex, called Chinese cordyceps or "DongChongXiaCao, " is not only a valuable traditional Chinese medicine, but also a major source of income for numerous Himalayan residents. Here, taking advantage of rapid advances in single-molecule sequencing, we assembled a highly contiguous genome assembly of O. sinensis . The assembly of 23 contigs was ∼110.8 Mb with a N50 length of 18.2 Mb. We used RNA-seq and homologous protein sequences to identify 8, 916 protein-coding genes in the IOZ07 assembly. Moreover, 63 secondary metabolite gene clusters were identified in the improved assembly. The improved assembly and genome features described in this study will further inform the evolutionary study and resource utilization of Chinese cordyceps.